THE IMPLEMENTATION OF DIFFERENTIATION IN TEACHING ENGLISH SUBJECT AT SD AL KHAIRIYYAH TAHFIDZ INTERNATIONAL KOTA TEGAL - Nurohmah, Siti; Fitriati, Sri Wuli; Bahri, Saeful (Language Circle: Journal of Language and Literature, 2025)
Abstract This study explored how differentiated instruction was implemented in the English subject at SD Al Khairiyyah Tahfizh International Full Day School Kota Tegal academic year 2024/2025. This study employed a qualitative descriptive research design to gain of how differentiated instruction is implemented in English sibject at SD Al Khairiyyah Tahfidz International, Kota Tegal. This research use qualitative data. The qualitative data were collected through teacher interviews, and student questionnaires. The participants consisted of five students and one teacher. The data were analysed and interpreted from the data finding. Based on the closed-ended questionnaire the teacher used the of differentiated instruction in the classroom. The study revealed that English teachers at SD Al Khairiyyah Tahfidz International apply differentiated instruction primarily through variations in content delivery, classroom activities, and assessment methods. Regarding to the finding the differentiated instruction approaches affect the student’s engagement in the English subject at SD AL Khairiyyiah. The differentiated instruction approach can help students more understand, comfortable, engaged and focused, helpful, flexible and creative. Implementing differentiated instruction presents several challenges for teachers. The teacher highlights that managing a large number of students is a primary concern, as the preparation of varied materials and activities for diverse learners demands significant time and effort. Overall, the research highlights the differentiated instruction to transform educational practices and improve learning to ensure equitable access and benefits for all students. The findings and discussion showed that the use of differentiated instruction makes students more understand, comfortable, engaged and focused, helpful, flexible and creative.